All optical clocked D flip flop for 1.72 Tb/s optical computing. (September 2020) - Damodaran, Saranya; T., Shankar; Anbazhagan, Rajesh
Abstract: In this paper, a novel clocked optical D flip flop using two dimensional photonic crystals has been proposed using unique alignment of line waveguide and ring resonator structures. By varying the dimension of the photonic crystal two novel structures are proposed to realize the functionality of clocked D flip flop. Moreover, the structures are investigated using silicon and chalcogenide glass. The proposed structure has the square lattice of 20 × 11 circular rods that is embedded in the air substrate. The flip flop using silicon structures display a contrast ratio of 11.13 dB and 3.353  dB at the Q and Q′ outputs. Alternatively, the structure using chalcogenide glass rods display a contrast ratio of 9.711 dB and 9.89  dB at the Q and Q' outputs. Bit rate of 1.72 Tb/s is obtained with the proposed D flip flop and the foot print is 11.4μm × 6.24 μm.